Przebaczenie i pojednanie Polaków i Ukraińców wobec zbrodni banderowskich = Forgiveness and reconciliation of Poles and Ukrainians in the context of Bandera crimes - Partacz, Czesław (1952- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
During the World War II, OUN-UPA Ukrainian nationalists inhabited inside the borders of the Second Polish Republic, murdered at least 134,000 Poles in Western Wołyń and Eastern Małopolska. Genocide has not been accounted for by the modern Ukrainian state, yet. It denies this crime of the OUN-UPA and make monuments of glory for the perpetrators of the crime. In the article the author enumerates the he conditions of forgiveness in Christianity and reconciliation that Ukrainians ought to fulfill.
Keywords: Ukrainian crimes; Banderian genocide; negation of the crimes by Ukrainians; the conditions of forgiveness in Christianity; zbrodnie ukraińskie; ludobójstwo banderowskie; negacja zbrodni przez Ukraińców; warunki przebaczenia w chrześcijaństwie